Computational studies on the gas phase reaction of methylenimine (CH2NH) with water molecules - Mohamad Akbar Ali (Nature Portfolio, 2020)
Abstract In this work, we used quantum chemical methods and chemical kinetic models to answer the question of whether or not formaldehyde (CH2O) and ammonia (NH3) can be produced from gas phase hydration of methylenimine (CH2NH). The potential energy surfaces (PESs) of CH2NH + H2O → CH2O + NH3 and CH2NH + 2H2O → CH2O + NH3 + H2O reactions were computed using CCSD(T)/6–311++G(3d,3pd)//M06-2X/6–311++G(3d,3pd) level. The temperature-and pressure-dependent rate constants were calculated using variational transition state theory (VTST), microcanonical variational transition state theory $$(μ VTST)$$ (μVTST) and Rice–Ramsperger–Kassel–Marcus/master equation (RRKM/ME) simulations. The PES along the reaction path forming a weakly bound complex (CH2NH⋯H2O) was located using VTST and $$μ$$ μ VTST, however, the PES along the tight transition state was characterized by VTST with small curvature tunneling (SCT) approach. The results show that the formation of CH2NH + H2O → CH2NH⋯H2O is pressure -and temperature-dependent. The calculated atmospheric lifetimes of CH2NH⋯H2O (~ 8 min) are too short to undergo secondary bimolecular reactions with other atmospheric species. Our results suggest that the formation of CH2O and NH3 likely to occur in the combustion of biomass burning but the rate of formation CH2O and NH3 is predicted to be negligible under atmospheric conditions. When a second water molecule is added to the reaction, the results suggest that the rates of formation of CH2O and NH3 remain negligible.